Finger cold-induced vasodilation test does not predict subsequent cold injuries: A lesson from the 2018 Canadian Forces Exercise. Issue 2 (3rd April 2019) - Sullivan-Kwantes, Wendy; Moes, Katy; Limmer, Robert; Goodman, Len
ABSTRACT: A cold–induced vasodilation (CIVD) test was administered to 113 Canadian Armed Forces (CAF) soldiers (age 25.6 ± 6 yrs) during pre-deployment to a Canadian Arctic training exercise. The incidence and rates/types of subsequent peripheral cold injuries, as well as the relationship of CIVD responses against other hypothesized/reported risk factors (smoking, gender, age, ethnicity and prior cold injury), were analyzed. Although there was a wide range of CIVD RIF (resistance index to frostbite) scores (mean = 5.0 ± 1.5), there were no systematic relationships between RIF and injury type/location and rate, and the other risk factors analyzed. The absence of physiological links to cold injury occurrence suggests that in a military cold deployment setting, other factors are in play, which might include clothing, training, leadership and doctrine. These factors should be examined in future work.